Upgrading Therapy Strategy Improves Pregnancy Outcome in Antiphospholipid Syndrome: A Cohort Management Study - Hoxha, Ariela; Favaro, Maria; Calligaro, Antonia; Del Ross, Teresa; Ruffatti, Alessandra Teresa; Infantolino, Chiara; Tonello, Marta; Mattia, Elena; Ruffatti, Amelia (Thrombosis and Haemostasis, 2020)
The current study evaluates the efficacy and safety of different treatment strategies for pregnant patients with antiphospholipid syndrome. One hundred twenty-seven consecutive pregnancies were assessed; 87 (68.5%) with a history of pregnancy morbidity alone were treated with prophylactic low molecular weight heparin (LMWH) + low-dose aspirin (LDA, 100 mg) (group I) and 40 (31.5%) with a history of thrombosis and/or severe pregnancy complications with therapeutic LMWH + LDA (group II). LMWH doses were increased throughout the pregnancies depending on the patients' weight gain, and treatment was switched to a more intensive one at the first sign of maternal/fetal complications. The study's primary outcome was live births. There were no significant differences in live birth rate between group I (95.4%) and group II (87.5%). Even fetal complication rate was similar in the two groups; group II nevertheless had a higher prevalence of maternal and neonatal complications (p = 0.0005 and p = 0.01, respectively) and registered a significantly lower gestational age at delivery and birth weight (p = 0.0001 and p = 0.0005, respectively). Two patients in group I switched to group II therapy, six patients in group II switched to a more intensive treatment strategy (weekly plasma exchange + fortnightly intravenous immunoglobulins in addition to therapeutic LMWH + LDA). The multivariate analysis uncovered that triple antiphospholipid antibodies positivity was an independent factor leading to a more intensive therapy. All eight switched patients achieved a live birth. Study results revealed that adjusted LMWH doses and switching therapy at first signs of severe pregnancy complications led to a high rate of live births in antiphospholipid syndrome patients.
Keywords: obstetric antiphospholipid syndrome; low molecular weight heparin; low-dose aspirin; plasma exchange; intravenous immunoglobulins; pregnancy